LEXICAL BUNDLES OF INDONESIAN AND ENGLISH RESEARCH ARTICLES: FREQUENCY ANALYSIS - azka saeful haq; Rosaria Mita Amalia; Susi Yuliawati (JALL (Journal of Applied Linguistics and Literacy), 2021)
This study is preliminary research of lexical bundles in the corpus of Indonesian and English research articles that focuses on analysis of frequency and distribution. This study aims to acquire list of common lexical bundles in applied linguistics articles and describes the patterns of bundle use. The most frequent lexical bundles investigated by frequency criteria reflect the common pattern of bundle use in each corpus. Frequency-based approach to multi-word combination enables us to acquire reliable results because of its statistical test in authentic language data. The result shows that the most numerous bundles are 3-word length and surprisingly, 5-word bundles it can be concluded that occurs in the top 20 rank in Indonesian corpus. The comparison between corpora reflects that the bundles across text section are identical. Although there are the same bundles used in both corpora, the typical bundles with high score of frequency and range are found to characterize the different group of writers. The distributional patterns show that there is the presence of popular bundles in English and Indonesian writers. The top rank lists emphasize that the common lexical bundle structures are phrase-based in expert level. Practically, this study can play role in English for Academic Purposes (EAP) to recommend prevalent patterns of lexical bundle use in the form of pedagogically useful list of word combination. The findings can also be used for non-native writers or scholars especially Indonesian writers to enrich the use of lexical bundles across sections in language and linguistics field.